Testing the sensitivity of charcoal as an indicator of fire events in savanna environments: quantitative predictions of fire proximity, area and intensity - Duffin, K; Gillson, L; Willis, K (SAGE Publications, 2008)
The charcoal record contained in lake sedimentary sequences is often used to infer past fire events. Studies to calibrate such charcoal records have been carried out in a range of mid- to high-latitude regions and relationships have been determined between size and quantity of charcoal in the sediment and proximity and spatial extent of the fire. Very little is known, however, about the relationship between fire events in savanna ecosystems and how these are represented in the charcoal record in lake sedimentary sequences. This study presents the results of a project that aimed to calibrate the micro- and macroscopic charcoal record from Kruger National Park, South Africa, with known fire events. Surface sediment samples were analysed for charcoal of different size classes and compared with data on fire proximity, area and intensity (the rate of energy released along a fire front) from fire events over the last 10 years, and the relevant source areas for micro- and macroscopic charcoal were quantified. Results indicated that (i) the Relevant Source Area of Charcoal for lakes c. 200 m diameter is between 0 and 5 km for charcoal particles ≥ 50μm in length and between 10 and 15 km for charcoal particles < 50μm; (ii) that charcoal deposits are most likely to represent combined fire events from the preceding five years, (iii) that fire proximity, area and intensity are each significantly represented in the charcoal record, but not equally, as the signal resulting from fire intensity is stronger than that for fire proximity or area. Mathematical equations linking charcoal with fire proximity, area and intensity are presented.